Rapid Characterization of Bacterial Electrogenicity Using a Single-Sheet Paper-Based Electrofluidic Array - Gao, Yang; Hassett, Daniel J.; Choi, Seokheun (Frontiers in Bioengineering and Biotechnology, 2017)
Electrogenicity or bacterial electron transfer capability creates potential important applications that offer environmentally sustainable advances in the fields of biofuels, wastewater treatment, bioremediation, desalination, and biosensing. Significant boosts in this technology can be achieved with the growth of synthetic biology that manipulates microbial electron transfer pathways and improves their electrogenic potential. What is currently needed is a high-throughput, rapid and highly sensitive test array to access the electrogenic properties of newly discovered and/or genetically engineered bacterial species. In this work, we report a single-sheet, paper-based electrofluidic (incorporating both electronic and fluidic structure) screening platform for rapid, sensitive, and potentially high-throughput characterization of bacterial electrogenicity. This novel screening array uses (i) a commercially available wax printer for hydrophobic wax patterning on a single sheet of paper and (ii) water-dispersed electrically conducting polymer mixture, poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), for full integration of electronic and fluidic components into the paper substrate. The engineered 3-D, microporous, hydrophilic and conductive paper structure provides a large surface area for efficient electron transfer. This results in rapid and sensitive power assessment of electrogenic bacteria from a microliter sample volume. We validate the effectiveness of the sensor array by using strategically genetic modified Pseudomonas aeruginosa mutant strains. Within 20 minutes, the sensor platform successfully determines the electricity-generating capacities of five isogenic mutants of P. aeruginosa while distinguishing their differences from control samples.